DYNAMICS OF TECHNICAL TRAINING OF YOUNG TENNIS PLAYERS OF GIRLS - Turobov Hatamjon Husanboyevich (Research Focus International Scientific Journal, 2023)
This is it in the article young tennis player of girls’ technical preparation dynamics universal and special tools using light up given. Research At the end of received results on the surface necessary instruction and recommendations statement done.